Expert systems - Vanda, Pindlova (Information & Media, 1994)
The expert systems were developing as on-line systems. They may be defined as intellectual systems based on knowledge. They help to make decisions in special fields of knowledge. The author of the article analyses the main factors which stimulated the development of the expert systems, their essence and structure. She gives the examples of such systems and their activity. The great attention is paid to the expert systems used in library and information work. Detailed description of PLEXUS - expert system designed in Central Information Service of London University is given.